MTE1 Functions with MPH1 in Double-Strand Break Repair. Issue 1 (1st May 2016) - Yimit, Askar; Kim, TaeHyung; Anand, Ranjith P; Meister, Sarah; Ou, Jiongwen; Haber, James E; Zhang, Zhaolei; Brown, Grant W
Abstract: Double-strand DNA breaks occur upon exposure of cells to ionizing radiation and certain chemical agents or indirectly through replication fork collapse at DNA damage sites. If left unrepaired, double-strand breaks can cause genome instability and cell death, and their repair can result in loss of heterozygosity. In response to DNA damage, proteins involved in double-strand break repair by homologous recombination relocalize into discrete nuclear foci. We identified 29 proteins that colocalize with recombination repair protein Rad52 in response to DNA damage. Of particular interest, Ygr042w/Mte1, a protein of unknown function, showed robust colocalization with Rad52. Mte1 foci fail to form when the DNA helicase gene MPH1 is absent. Mte1 and Mph1 form a complex and are recruited to double-strand breaks in vivo in a mutually dependent manner. MTE1 is important for resolution of Rad52 foci during double-strand break repair and for suppressing break-induced replication. Together our data indicate that Mte1 functions with Mph1 in double-strand break repair.